Adipokines, Oxidized Low-Density Lipoprotein, and C-Reactive Protein Levels in Lean, Overweight, and Obese Portuguese Patients with Type 2 Diabetes. (17th January 2013) - Neuparth, Maria João; Proença, Jorge Brandão; Santos-Silva, Alice; Coimbra, Susana
Abstract : Aim . Our aim was to study how different BMI scores may influence the levels of inflammation, oxidative stress, adipogenesis, glucose, and lipid metabolism, in lean, overweight, and obese Portuguese patients with type 2 diabetes mellitus (T2DM). Methods . We studied 28 lean, 38 overweight, and 17 obese patients with T2DM and 20 controls (gender and age matched). The circulating levels of oxLDL, CRP, and some adipokines—adiponectin, leptin, and chemerin—and the lipid profile were evaluated. Results . Obese patients presented significantly lower levels of adiponectin and higher leptin, oxLDL, and chemerin levels, as compared to the overweight, lean, and control groups. Overweight, compared to lean and control, subjects showed significantly lower adiponectin and higher leptin and chemerin levels; oxLDL values were significantly higher in overweight than in lean patients. Lean patients presented significantly higher chemerin values than the control. Obese patients presented significantly higher CRP values, as compared to lean patients and the control group. Obese and overweight patients presented significantly higher triglycerides values than lean patients. Except for CRP, all the observed significant changes between control and patients remained significant after statistical adjustment for the body mass index (BMI). Conclusion . The levels of leptin, adiponectin, oxLDL, CRP, and triglycerides in patients with T2DM seem to be more associated with obesity and less with diabetes. Chemerin levels were raised in lean, overweight, and obese patients, suggesting that, independently of BMI, an adipocyte dysfunction occurs. Moreover, chemerin may provide an important early biomarker of adipocyte dysfunction and a link between obesity and type 2 diabetes mellitus.